Chemical Vapor Deposition - Recent Advances and Applications in Optical, Solar Cells and Solid State Devices 2016
DOI: 10.5772/64654
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Enhanced Chemical Vapor Deposition: Where we are and the Outlook for the Future

Abstract: Chemical vapor deposition (CVD) is a technique for the fabrication of thin films of polymeric materials, which has successfully overcome some of the issues faced by wet chemical fabrication and other deposition methods. There are many hybrid techniques, which arise from CVD and are constantly evolving in order to modify the properties of the fabricated thin films. Amongst them, plasma enhanced chemical vapor deposition (PECVD) is a technique that can extend the applicability of the method for various precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 142 publications
(226 reference statements)
0
14
0
1
Order By: Relevance
“…The wide range of NPs can be formed via this method, for instance gallium nitride and so forth [70]. The expensive instrumentation, instability in damp conditions, presence of poisonous gases in plasma stream and lengthy process are some of the shortfalls of the method [71].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The wide range of NPs can be formed via this method, for instance gallium nitride and so forth [70]. The expensive instrumentation, instability in damp conditions, presence of poisonous gases in plasma stream and lengthy process are some of the shortfalls of the method [71].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…PECVD-deposited thin films' high quality and superior properties are governed by various parameters including RF power, plasma temperature, reactor pressure, gas phase diffusion, and gas flow rate in addition to the types of carriers and reacting gases. Typically, the neutrally charged and highly energetic plasma used during PECVD thin films deposition is a partially or totally ionized gas composed of charged particles, electrons, and neutral atoms constituents (Hamedani et al, 2016).…”
Section: Fundamental Principlesmentioning
confidence: 99%
“…Plasma enhanced chemical vapor deposition (PECVD) involves the decomposition of the precursor molecules by charged gas particles (plasma), the contact with plasma could occur either at the layer above the substrate, or the precursor reactants could be absorbed to the substrate and consequently decomposed to form the coating film (Hamedani et al, 2016). Mathur and Kuhn (2006) after depositing titanium oxide coatings on steel substrates, via thermically activated CVD at 450 -500 0 C and plasma assisted CVD at 200 0 C observed that the PECVD produced a better structured, homogenous, smoother and denser coating than TCVD.…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%